Taxonomic revision of the Afrotropical genus Pseudagris de Saussure (Hymenoptera: Vespidae: Eumeninae), with description of four new species - Selis, Marco (Zootaxa, 2023)
The Afrotropical genus Pseudagris de Saussure, 1863 is revised. Four new species, Pseudagris apicalis sp. nov., Pseudagris nigrithorax sp. nov., Pseudagris nigrorufa sp. nov., and Pseudagris tanzanica sp. nov., are described. The following taxonomic changes are proposed: Pseudagris versicolor (von Schulthess, 1914) = Synagris versicolor var. meade-waldoi Maidl, 1914 syn. nov.; Pseudagris tessmanniana (von Schulthess, 1913) stat. rev. et comb. nov. is resurrected from synonymy. Lectotypes for Synagris aterrima Maidl, 1914 and Synagris versicolor von Schulthess, 1914 are designated. The males of Pseudagris brunnea Gusenleitner, 2007 and Pseudagris carinata (de Saussure, 1863), and the female of P. pygmaea Gusenleitner, 1998 are described for the first time. A key to the species is provided.